2004
DOI: 10.1023/b:emas.0000009233.98215.1f
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Expansion of Water Quality Monitoring Network by Fuzzy Optimization Approach

Abstract: Abstract. River reaches are frequently classified with respect to various mode of water utilization depending on the quantity and quality of water resources available at different location. Monitoring of water quality in a river system must collect both temporal and spatial information for comparison with respect to the preferred situation of a water body based on different scenarios. Designing a technically sound monitoring network, however, needs to identify a suite of significant planning objectives and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The proposed monitoring network design methodology incorporates uncertainties as random errors. However, a more rigorous analysis may be accomplished by adopting soft computing techniques such as fuzzy logic (Ning and Chang 2004) and grey system theory (Chang and Hernandez 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed monitoring network design methodology incorporates uncertainties as random errors. However, a more rigorous analysis may be accomplished by adopting soft computing techniques such as fuzzy logic (Ning and Chang 2004) and grey system theory (Chang and Hernandez 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, we can point out the use of several optimization methods (for instance, multiobjective optimization, integer programming or fuzzy optimization) to assess locating strategies of monitoring networks in the river basin. An extensive literature review on application of optimization methods to this issue can be found, for instance, in the works of Chang et al [7,[17][18][19] and the references therein, including recent advances in revised methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…There were also some other related researches reported, but most of them had not applied an optimization-based approach (Warry and Hanau 1993;Loftis et al 1991;Whitlach 1989;Lettenmaier et al 1984;Sanders et al 1983;Lettenmaier 1978;Lettenmaier and Burges 1977). Although some other researches had applied optimization models to determine the locations of sampling sites, the identification capability to locate the source of a detected pollution event is still not considered (Strobl et al 2006;Icaga 2005;Ning and Chang 2002, 2004, 2005. As described by Dixon et al (1999), the method proposed by Sharp (1971) may not be capable of locating the optimal placement of sampling sites.…”
Section: Introductionmentioning
confidence: 99%